IMPROVEMENT OF EQUIPMENT FOR EFFECTIVE HARDENING SAND MIXTURE BY VACUUM MOLDING - V. S. Doroshenko (Литьë и металлургия)
The review deals with the design flask tooling and patterns for effective hardening sand mixture in the vacuum molding (V-Process), and molding on a one-off patterns (Lost Foam Casting). Sealing and evacuating sand mixture – two major factors influence the strength of the casting mold and casting quality, management practices which will enable to improve the casting process.